A Decomposition Approach to Cause-Specific Mortality in the Port City of Antwerp in the Early 20th Century - Devos, Isabelle (Historical Life Course Studies, 2025)
Building on Janssens' work, which highlights the distinct epidemiological profiles of port cities, this study explores cause-specific mortality in early 20th-century Antwerp, Belgium's largest city and a major international port. Using Arriaga's decomposition method, we compare life expectancy and mortality by cause of death in Antwerp with those in Brussels, Ghent, and Liège, the country's next three largest cities. Despite its status as a bustling port city, Antwerp showed a relative health advantage. However, this advantage masked gender- and age-specific risks. Young adult men experienced elevated mortality from accidents, largely due to hazardous port labor, while women faced excess mortality from childbirth, likely linked to socioeconomic vulnerabilities among working-class and immigrant women. Notably, child mortality from infectious diseases was higher in Antwerp than in the other three cities, reflecting particular public health challenges. These findings highlight the importance of individual-level data to better understand localized mortality and cause-of-death patterns. They also underscore the need for further comparative research within the frameworks of the SHiP and Great Leap networks.